The effects of fermented milk containing Lactococcus lactis subsp. cremoris FC on defaecation in healthy young Japanese women: a double-blind, placebo-controlled study. (18th August 2018) - Ozaki, Kaoru; Maruo, Toshinari; Kosaka, Hideki; Mori, Mari; Mori, Hideki; Yamori, Yukio; Toda, Toshiya
Abstract: The objective of this double-blind, placebo-controlled study was to elucidate the effects of fermented milk containing Lactococcus lactis subsp. cremoris FC (FC) on defaecation in healthy young women. We included 31 women (18–31 years old) who were randomly selected into two groups. Subjects in the test group consumed fermented milk containing FC, while subjects in the placebo group consumed non-fermented gelled milk. In the test group, defaecation frequency (both in days and times per week) and stool volume significantly increased during the consumption of fermented milk containing FC compared with before consumption. These effects were also observed in subjects with mild constipation. Furthermore, in subjects with mild constipation, stool ammonia concentration was significantly lower in the test group than that in the placebo group after 4 weeks. These results suggest that fermented milk containing FC is beneficial for improving defaecation and faecal properties.